2018
DOI: 10.1242/jcs.211094
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear phosphatidylinositol 4,5-bisphosphate islets contribute to efficient RNA polymerase II-dependent transcription

Abstract: This paper describes a novel type of nuclear structure - nuclear lipid islets (NLIs). They are of 40-100 nm with a lipidic interior, and phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P] molecules comprise a significant part of their surface. Most of NLIs have RNA at the periphery. Consistent with that, RNA is required for their integrity. The NLI periphery is associated with Pol II transcription machinery, including the largest Pol II subunit, transcription factors and NM1 (also known as NMI). The PtdIns(4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 91 publications
4
78
0
Order By: Relevance
“…Based on our data we concluded that the observed C. elegans phenotypes might be caused by (i) the altered chromosome structure; (ii) impaired ubiquitin-proteasome pathway; or (iii) disrupted binding of PIP2 to some essential proteins. Based on our data presented here and already published data in mammalian cell lines [ 16 , 17 , 18 ], we propose that PIP2 is involved in the regulation of the molecular processes at multiple levels, and may be a part of many protein complexes in the C. elegans germ cells nuclei.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Based on our data we concluded that the observed C. elegans phenotypes might be caused by (i) the altered chromosome structure; (ii) impaired ubiquitin-proteasome pathway; or (iii) disrupted binding of PIP2 to some essential proteins. Based on our data presented here and already published data in mammalian cell lines [ 16 , 17 , 18 ], we propose that PIP2 is involved in the regulation of the molecular processes at multiple levels, and may be a part of many protein complexes in the C. elegans germ cells nuclei.…”
Section: Discussionsupporting
confidence: 61%
“…However, we did not observe any obvious asymmetrical localization of PIP2 in the embryos, and thus provide more support for another proposal, that PPK-1 might influence the spindle positioning independently of its function as a PIP2 producer. Suggestions about the independent role of PI5PK and PIP2 were previously published by us [ 18 ] and Chakrabarti et al for the regulation of the RNA polymerase I transcription in mammalian cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings raise a number of intriguing questions on the localization and physical organization of lipids in the nucleus; however, an increasing on June 18, 2020 at SYDDANSK UNIVERSITETSBIBLIOTEK http://mcb.asm.org/ Downloaded from body of literature points to the presence of specific bioactive lipids in the nucleus [46][47][48][49]. Moreover, studies in mammals have also detected neutral sphingomyelinase (the mammalian counterpart of ISC1) [50][51][52][53][54] and sphingomyelin in the nucleus [55].…”
Section: Functional Annotation Of the 190 Proteinsmentioning
confidence: 99%